Hunger and Food Well-Being: Advancing Research and Practice. (April 2019) - Bublitz, Melissa G.; Hansen, Jonathan; Peracchio, Laura A.; Tussler, Sherrie
This article explores the paradigm of Food Well-Being (FWB), "a positive psychological, physical, emotional, and social relationship with food, " for those who experience hunger. Building on the insights derived from two sources—research across a range of disciplines including marketing and the practices of the nonprofit Hunger Task Force to alleviate hunger and advance FWB—the authors explore the five domains of FWB: food availability, food socialization, food literacy, food marketing, and food policy as they relate to people who experience hunger. The authors establish a research contribution by extending the FWB paradigm to include people experiencing hunger and by applying this extended paradigm to illuminate the impact of hunger on people's FWB. Finally, the authors propose research to guide researchers, policy makers, and nonprofits toward generating FWB for all.